Identity and School Discourse: Does Vernacular Linguistic Heritage Undermine Educational Communication within Classrooms? - Aboubker, Taoufik (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2025)
This study examines the impact of vernacular linguistic heritage on educational communication within classrooms by exploring the interference between Standard Arabic and local dialects. It aims to deconstruct the tension between what is expected to be a coherent pedagogical discourse and a linguistic reality shaped by the sociological environment, which often renders educational communication vulnerable to confusion and disruption. Central questions addressed in the study include: How can a balance be achieved between Standard Arabic and pedagogical interaction under the dominance of vernacular linguistic heritage? To what extent does the use of vernacular terminology hinder and fragment educational communication? How capable are teachers of maintaining equilibrium between learner interaction and the use of standard linguistic concepts? The study focuses on three main axes: School discourse between colloquial and formal communication; The diglossic divide between Standard Arabic and vernacular dialects and its impact on educational communication; Toward a pedagogical approach to balancing Standard Arabic with classroom interaction. The research adopts a descriptive-analytical methodology, drawing on theoretical analysis of linguistic and educational literature and observing classroom practices from a descriptive perspective. The approach provides an analytical and theoretical dimension aimed at uncovering the pedagogical implications of this phenomenon and proposing alternative strategies to address it. Findings indicate that functionally integrating vernacular linguistic heritage within classroom practices can serve as a pedagogical entry point for gradually developing mastery of Standard Arabic. This approach simultaneously achieves two objectives: preserving Standard Arabic –- which is experiencing notable decline –- and encouraging active learner participation by transforming colloquial concepts into standard equivalents, fostering a linguistic synthesis that safeguards Standard Arabic while supporting pedagogical interaction.